Heat Exposure and Predictors of Heat-Related Illness Symptoms among Outdoor Municipal Workers - Nurul Izzah Abdul Samad; Anis Adiba Adnan; Nursuhaili Mohd Amin; Maisarah Nasution Waras; Nurul Atikah Che Hasan; Nurhidayah Sabri; Herdianti Hatta; Nurul Ainun Hamzah (Universitas Airlangga, 2026)
Introduction: Municipal workers who perform outdoor tasks daily are often exposed to hot weather conditions, which may contribute to various heat-related illnesses (HRI). Long working hours in hot and humid environments may affect workers physically through dehydration, fatigue, heat exhaustion, and other symptoms related to heat strain. This study was conducted to assess environmental heat exposure and factors associated with HRI symptoms among outdoor sanitation and maintenance workers. Methods: A cross-sectional study was carried out among 88 outdoor municipal workers in Kota Bharu, Kelantan. Environmental heat exposure was measured using the Wet Bulb Globe Temperature (WBGT) index. Data was collected using a self-administered questionnaire covering sociodemographic characteristics, work-related profiles, and heat-related illness (HRI) symptoms experienced after the work shift. Multiple logistic regression analysis was applied to identify factors associated with HRI symptoms. Results and Discussion: WBGT values recorded during both work sessions ranged from 29.99°C to 30.54°C, were close to or exceeding the recommended occupational exposure limits. Most workers reported at least one mild HRI symptom (96.6%), with fatigue, dizziness, and muscle cramps being the most reported complaints. The analysis showed that effective WBGT (WBGTeff) was significantly associated with HRI symptoms (p = 0.043). Conclusion: Outdoor municipal workers were exposed to considerable environmental heat, which may contribute to heat-related symptoms. Preventive strategies such as adequate hydration and appropriate work-rest arrangements, and heat awareness programs should be strengthened to reduce the risk of heat-related illness among workers.